Water Quality Analysis Relation To Phytoplankton Community And Fish Resources in Teluk Gelam Lake, Ogan Komering Ilir - Septika Putri Anggraini; Suheryanto Suheryanto; Herpandi Herpandi (Program Pascasarjana Universitas Sriwijaya, 2021)
This study aimed to analyze the quality of the waters and its relationship with the structure of phytoplankton communities and fish resources. This research was conducted in March 2021 at lake Teluk Gelam Ogan Komering Ilir. Phytoplankton sampling has been done once with 3 replays and there are 5 station points. Measurement of water quality parameters physical and chemical waters include temperature, pH, dissolved oxygen (DO), ammonia, brightness, turbidity, depth, nitrite, nitrate, and phosphate. Water quality analysis was calculated using the pollution index method (IP) and evaluated based on environmental quality standards according to the Decree of the State Minister for the Environment Number 115 of 2003. Based on the results of research that have been conducted in the lake Teluk Gelam district Ogan Komering Ilir that the overall average parameters of water quality in the lake were still an adequate condition for the life of organisms, especially phytoplankton. And based on the observations on the composition of phytoplankton structures in the waters of the lake Teluk Gelam found 3 classes of phytoplankton consisting of Bacillariophyceae, Chlorophyceae, and Cyanophyceae with a varied number of genera, while the fertility level of Teluk Gelam lake waters is included in the eutrophic category.